2009
DOI: 10.1590/s1678-77572009000100004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of periodontal parameters in individuals with syndromic craniosynostosis

Abstract: Craniosynostosis syndromes are characterized by premature closure of one or more cranial sutures, associated with other malformations, the most frequent of which are the Crouzon and Apert syndromes. Few studies in the literature have addressed the oral health of these individuals. The purpose of this study was to compare the periodontal status of individuals with Apert, Crouzon, Pfeiffer and Saethre-Chotzen syndromes before toothbrushing and compare the efficiency of plaque removal before and after mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
2
3
0
2
Order By: Relevance
“…Múfalo et al . (32) found that the left quadrants showed significantly higher levels of plaque than the right quadrants due to a predominance of right‐handed subjects (in the present series, 92 percent of the subjects were right‐handed) and the effect this has on the performance of techniques of oral hygiene. In consequence, in terms of plaque, calculus and, probably, gingival inflammation, Q1 would be the least affected and Q3 the most affected; this combination would therefore be the optimal selection for evaluation of these clinical parameters.…”
Section: Discussionmentioning
confidence: 38%
“…Múfalo et al . (32) found that the left quadrants showed significantly higher levels of plaque than the right quadrants due to a predominance of right‐handed subjects (in the present series, 92 percent of the subjects were right‐handed) and the effect this has on the performance of techniques of oral hygiene. In consequence, in terms of plaque, calculus and, probably, gingival inflammation, Q1 would be the least affected and Q3 the most affected; this combination would therefore be the optimal selection for evaluation of these clinical parameters.…”
Section: Discussionmentioning
confidence: 38%
“…Regarding periodontal aspect, the OHI-S scores of CS patients were significantly higher than those in healthy children and also higher than scores reported in the Thai national oral health survey (2017). These can be postulated that the CS patients are prone to have poor oral hygiene which consistent with previous studies (10,78). Obstacles in oral cleaning mentioned by patients and care givers include abnormal facial anatomy, small mouth, tooth crowding, and risk of aspiration.…”
Section: Chapter V Discussionsupporting
confidence: 85%
“…Supervision by a pediatric dentist in early childhood is critical in order to ensure satisfactory oral hygiene of patients with syndromic craniosynostosis. Because of the anatomical discrepancies, these patients present decreased upper arch dimensions which lead to crowding, delayed and ectopic eruptions with implied propensity for periodontal disease 60 .…”
Section: Dental Managementmentioning
confidence: 99%